Correlação entre diferentes métodos de avaliação da composição corporal e indicadores antropométricos em escolares - Thiago Henrique de Oliveira (2010)
This study aimed to describe the nutritional status and to correlate different methods of assessing body composition and anthropometric indicators in a sub-sample of schoolar children, with the reference method a tetrapolar bioimpedance. A cross-sectional study was development with a convenience sample of the 89 children with aged 7 to 11 years in urban area of Ouro Preto city, Minas Gerais. Data collection was taken with the assessment of anthropometric parameters and body composition whose measurements were made by previously trained evaluators. A single evaluator measured weight (kgf), % Body fat byTanita (bipedal bioimpedance) and a height (cm); the second examiner was responsible for the measures of skinfold thicknees and hip circumference and waist circumference. The third examiner was responsible for data collection by tetrapolar bioelectrical impedance analysis. After the measurements of weight and height, all children were classified according to the percentile values of body mass index (BMI) by sex and age. We obtained the percentage of body fat (% BF) by bioimpedance tetrapolar, Tanita (bipedal bioimpedance) and skinfoldthicknees. We assessed anthropometric indicators: body mass index (BMI), conicity index (IC), waist/ height ratio (WHR) and waist-hip ratio. The descriptive results were obtained using frequencies and percentages, besides that, we used the Kolmogorov-Smirnov, Mann-Whitney, Student t, and Ryan-Joiner tests and correlation coefficients of Person and Spearman. For the multivariate analysis we used two methods for automatic selection Best Subsets and Stepwise Backward. In this study there was a balance in relation to the number of male (n = 44) and female (n = 45). Of the 89 children evaluated 15.7% were (eutrofic), 54% (overweight) and 30.3 % (obese). The average age of the study group was 8.5 years for females and 8.7 years for males. We found statistically significant differences between the sexes for the variables: % BF by tetrapolar bioelectrical impedance, % BF by Tanita (bipedal bioimpedance), % BF by skinfold thickness and waist-hip ratio. At 6% the WHR was statistically significant. In this study, it seems that higher averages the IC, WHR were for girls and we arent noticed a decrease IC with advancing age. The correlation coefficients between % BF tetrapolar bioelectrical impedance, % BF by Tanita (bipedal bioimpedance) and % BF by skinfold thickness were (r = 0, 694 and r = 0, 588). There wasnt statistically significant correlation between % BF by tetrapolar bioelectrical impedance, age, waist-hip ratio and poor correlations were found between % BF by tetrapolar bioelectrical impedance and weight (r=0,297; p 0,05). As regards the correlations between % BF by tetrapolar bioimpedance, WHR, IC, BMI in this study found moderate correlations (r = 0.715, r = 0.673, r = 0.529). In conclusion, this study that the highest correlations with a % BF by tetrapolar bioelectrical impedance were found with a variables: WHR, % BF by Tanita (bipedal bioimpedance), IC, BF % skinfold thickness and BMI with values correlation (r = 0, 715, r = 0, 694, r = 0, 673, r = 0, 588, r = 0, 529) respectively